The Validity of Terms and Conditions in Online Loan Applications Under the Indonesian Civil Code - Raroza Amanda; Nur Annisa; Zita Gus Laura; Elsa Antoni; Debby Fitrianti (Verdict: Journal of Law Science, 2026)
Online loan applications use standard-form Terms and Conditions to form credit relationships, obtain borrower consent, allocate risk, regulate data access, and define repayment consequences. This article examines whether such Terms and Conditions are valid under the Indonesian Civil Code, particularly Articles 1320 and 1338, through doctrinal legal analysis based on statutory interpretation, systematic interpretation, conceptual construction, and clause-based legal reasoning. The study assesses electronic assent, standard-form clauses, data authorization, and repayment obligations against the Civil Code requirements of consent, capacity, definite object, lawful cause, good faith, and contractual fairness. The analysis finds that Terms and Conditions may be valid when the borrower receives conspicuous notice, gives affirmative consent, has legal capacity, and agrees to a determinable loan object and lawful cause. Validity becomes vulnerable when clauses obscure economic costs, authorize excessive unilateral changes, impose disproportionate penalties, transfer all platform liability, or collect personal data beyond the financing purpose. The theoretical contribution of this article is a layered Civil Code validity framework that connects formal electronic consent with substantive good faith, proportionality, transparency, and consumer protection. The article proposes a six-part validity test: conspicuous notice, active consent, accessible language, determinable object, lawful data processing, and proportional risk allocation.